Field Diary: construction and utilization in scientific researches. Bibliographic analysis - Adriana Roese; Tatiana Engel Gerhardt; Aline Corrêa de Souza; Marta Julia Marques Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This article emerged from the author's necessity of finding bibliography reference which were related to the construction and utilization of field diary as a complementary instrument in scientific researches. It had the objective of doing a bibliographic review referring to its utilization and describing experiences of the use of those methodological instruments. For that, it was developed a conceptual reference, an item dealing with the construction of a field diary and other a report on the experiences which the authors had with its use. We believe this study may help other researchers who search to develop researches with this data collector instrument.